Potential mechanism of action of antimicrobial peptide through computer-assisted method: article - Md Yusof, Jamaliah; Tan, Huey Ling (2018)
This research have been carried out to study the mechanism of actions of antimicrobial peptides using bioinformatics technique. The aim of this research is to determine and visualize the 3-dimensional structure of the secondary structure of the antimicrobial peptide, to classify and compare the antimicrobial peptides based on the secondary structure: α-helical, β-strand, α+β structure and non-α+β structure and to determine the effect of net charge of the antimicrobial peptides on their mechanism of action. The mechanism of action of antimicrobial peptides has studied by bioinformatics techniques, using any related databases such as APD, PDB, UniProt and DBAASP. The results shows that most of antimicrobial peptides are α-helical and α+β secondary structure. The peptides are also cationic which makes them interact with negative-charges of bacterial cell membranes.